Benjamin Franklin, 1706-2008 : anatomie d’un tricentenaire transatlantique - Marie-Jeanne Rossignol (Transatlantica)
This paper offers reflections on the Benjamin Franklin Tercentenary, which took place from 2006 to 2008. This anniversary was celebrated by many publications, conferences and exhibitions in the United States, producing a renewed and critical understanding of Franklin, “not your usual founding father”. The main exhibition travelled to France (2007-2008), clearly as part of an attempt to patch up relationships between the two countries in the wake of the Iraq war controversy. The main focus in this Franco-American commemoration was on transatlantic diplomacy and collaboration, not really on Franklin in his multiple capacities, in his time and country of birth. The conference organized at Université Paris-Diderot in January 2008 was by contrast a scholarly affair, highlighting work on Franklin conducted by French and foreign specialists. Most of the papers are presented here.